Does violation of regulations hurt firm value enhanced: Evidence from Taiwan banking industry? - Ni, Yensen; Fan, Yangchu; Liao, Yulu; Hsu, Yu-Min (Eximia, 2023)
This study investigates the impact of penalties, including sanctions, corrections, and fine payments, on firm value within the context of the banking industry on the Taiwan Stock Exchange (TWSE) from 2017 to 2021. Utilizing data from the Financial Supervisory Commission, we employ rigorous statistical methods, such as multiple regression and Petersen regression models, to discern whether these punitive measures affect firm performance. Intriguingly, our findings indicate that firms subject to financial sanctions and penalties in Taiwan experience an improvement in their firm value, challenging the conventional belief that such penalties erode value. We propose that this unexpected outcome may be attributed to the potential gains derived from expanding business activities, even in violation of banking regulations, outweighing the associated regulatory costs. By shedding light on this under-researched aspect of the literature, our study contributes to a broader understanding of how regulatory penalties impact firm value in the banking industry, thereby providing regulatory authorities with practical insights.